Estado nutricional e desenvolvimento das habilidades motoras orais para a alimentação em crianças nascidas pré-termo - Ferreira, Pâmela Fantinel (2016)
Objectives: Ascertain the nutritional status and oral motor abilities development of preterm children and the association between them, in addition to investigate the maternal variables, feeding type, nursing nipple use and food intake markers during the first year of life. Methodology: descriptive and longitudinal study. Were included 45 children accompanied in a hospital in Southern Brazil, from July 2014 to March 2016 in six stages: birth (M1), hospital discharge (M2), 4 (M3), 6 (M4), 9 (M5 ) and 12 months of corrected age (M6). The data of birth and hospital discharge were collected from medical records. Anthropometric evaluations were conducted, assessment of oral motor skills with Schedule for Oral Motor Assessment (SOMA) protocol and application of food and socioeconomic questionnaire. Results: The average gestational age at birth was 32.9 (± 1.8) weeks and the average weight of 1751 (± 497) grams. Most were female (53.3%), classified as appropriate for gestational age (68.8%). In M2, was observed a significant increase On the sector (M3) the growth was resumed, significantly in weight (p <0.001) compared with M2 and cephalic perimeter (p = 0.016) compared to M1. The percentage of children at risk of overweight (BMI/A) was 11% in M3, 13% in M4 and 23% in M5 (p = 0.039), falling to 13% by M6. Overweight, appeared in 4% of children aged 9 and 12 months of CA (M5 and M6). The HMO evaluation showed that in M3, 78% had OMD, significantly decreasing to 41% (p <0.001) in M4. OMD was not associated with nutritional status in the first year of life. The type of prevalent feeding in the first year was the artificial, occurring early weaning at 4 months. The OMD was not associated with the type of feeding. The complementary feeding was introduced in chronological age on average 5.2 ± 1.2 months, and the CA on average 3.6 ± 1.3 months. In M3, 77.8% used a nursing nippler. Among these, 87.5% were not breastfed (p = 0.022). Nursing nipplers use was not associated with the presence of OMD (p = 0.058) at 4 months. At 12 months 42% consumed soft drinks, 44% artificial juice, 78% honey / molasses / sweets. At this age, 18% consumed cereal added to milk. Most consumed beans, meat, vegetables and fruits since 6 months old. Risk markers consume was not associated with nutritional status. Neonatal and maternal variables were not associated with the type of feeding and OMD on the studied times. Conclusion: Good oral motor performance occurred concomitantly with adequate nutritional status during the first year. The observed overweight and low quality food justify the monitoring of preterm children, mainly due to its relationship with chronic diseases throughout life. The health team should promote greater incentive to breastfeeding, avoiding early weaning and the appearance of deleterious oral habits.